Environmental Study of Effect of Some Plants Extracts on Culex pipiens mosquitoes (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2022)
Background       In the nature there are many plants that play important roles to control mosquitoes, but some of these plants can increased their effect after mixed with another plant. For that, this study aimed to know the effect of mixture of two types of different plants on Culex pipiens mosquitoes in the larva stages and the process of hatching the eggs.   Materials and methods  In this research the effect of parsley water extract (Petroselinum crispum) and mosses water extract (Funaria sp.) have been taken as mixture in ratio (1:1) to know their effect on Culex pipiens mosquitoes after using different concentrations (4.5, 3.5, 2.5, 1.5, 0.5) mg/l from it.Results The results show that percentage of mortalities for C. pipiens larva mosquitoes were (89, 72, 55, 42, 39)%, (89, 62, 56, 36, 38)%, (75, 67, 54, 46, 26)% and (77, 65, 63, 56, 40)% with LC50 (1.8, 2, 2.3, 1.3) mg/l for first, second, third and fourth stage respectively. While the percentage of hatching eggs that exposed to mixture extracts were (31, 43, 65, 71, 83)% with LC50 (3.2) mg/l. Results haven’t shown a significant differentiation among percentage of larva mortalities stages, but they have shown among percentage of hatching eggs in level of probability (0.05), also concentrations have a positive correlation coefficient with percentage of larva mortalities stages and negative with percentage of hatching eggs. ConclusionThe water extract mixture from water extract of parsley and mosses can be killed larva stages in low concentration and the mortality increases with increased concentration of extract, and can prevented eggs hatching.